Conflict of Jurisdiction in a Lawsuit for Violation of Personal Rights - Hamed, Abdullah Fadel (Journal of Legal and Political Studies, 2017)
The cross-border infringement of personality rights raises many problems concerning the jurisdiction of the courts. The research was concluded to the inadequacy of nationality as a criteria to determine the jurisdiction in general and in personality rights infringement specifically, and the venue of the defendant as a criteria of the jurisdiction must be at least his habitual residence which is Iraqi law contrary to that, because Iraqi law take in consideration mere presence of the defendant in Iraq. Also the research concluded that the criteria of "the place of the harmful event" raises some problems on the lawsuit of personality rights infringement when the elements of responsibility are distributed in more than one country, which is called comparative judiciary to interpreting it with the nature of the infringement of personality rights.
Keywords: Jurisdiction; responsibility,infringement; Nationality